APPLYING THE GENETIC ALGORITHM AND QUANTUM CHEMICAL CALCULATIONS TO STUDY THE STRUCTURE OF THE Sc2B6 CLUSTER AND ITS CO ADSORPTION - Minh Thao Nguyen; Tho Thanh Bui; Trung Cang Phan; Sy Linh Ho (Tạp chí Khoa học Đại học Đà Lạt)
We used the genetic algorithm and quantum chemical calculations to study the structures of the Sc2B6 cluster. The global minimum energy structure has the shape of a hexagonal bipyramid with an Sc atom at each apex and a B6 ring that belongs to the D6h point group symmetry. The second most stable structure has the Cs point group symmetry and can be formed by substituting a Sc atom for a B atom in the ring and a B atom for Sc in one of the apexes. From the computational results, the Sc2B6 cluster is found to be a good candidate to form a nanomaterial for treating CO gas.